Franchise Registration in the Perspective of Regulation of the Minister of Trade Number 71 of 2019 - Nirwana Dewi Harahap; Zetria Erma (LEGAL BRIEF, 2022)
The franchise business is one of the most visible concrete examples in export and import trade between countries globally. To guarantee the interests of the parties, this business needs to be registered in accordance with the applicable laws and regulations. This type of research is normative with a conceptual and statutory approach. The data used is secondary data consisting of primary, secondary and tertiary legal materials. In Article 11 of the Minister of Trade Regulation Number 71 of 2019 concerning Franchise Management, it is stated that a Franchise Registration Certificate (STPW) is issued by the OSS Institution for and on behalf of the Minister or Regents and Mayors. STWT application process submitted through the Online Single Submission (OSS) Institution. For this reason, it is recommended that the franchisor and franchisee register their businesses in accordance with applicable regulations and that local governments are more active in socializing franchise registration and exercising tighter supervision of franchisors and franchisees who do not register their businesses